Que faire d’exilés indésirables ? - Jeanne Moisand (Diasporas: Circulations, Migrations, Histoire)
This article studies the arrival of nearly two thousand Spanish republicans in French Algeria after the failure of a revolution in 1874. It shows how the French and Spanish authorities cooperate to make this stay as short as possible. Interned in military forts, several hundred refugees are subject to extradition measures and deported to the Spanish prison of Ceuta. The largest part of the group is moved by the army to the provinces of Alger and Constantine to work in public works camps. Many ask to be repatriated, a measure that conceals the expulsion.